2010
DOI: 10.1371/journal.pone.0011453
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells in Chronic Mycobacterial Granulomas Restrict Local Anti-Bacterial T Cell Response in a Murine Model

Abstract: BackgroundMycobacterium-induced granulomas are the interface between bacteria and host immune response. During acute infection dendritic cells (DCs) are critical for mycobacterial dissemination and activation of protective T cells. However, their role during chronic infection in the granuloma is poorly understood.Methodology/Principal FindingsWe report that an inflammatory subset of murine DCs are present in granulomas induced by Mycobacteria bovis strain Bacillus Calmette-guerin (BCG), and both their location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
41
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 84 publications
3
41
0
2
Order By: Relevance
“…Indeed, mycobacterial infection induces a delicate equilibrium between proinflammatory and anti-inflammatory immune responses, and this is well illustrated in pulmonary granulomas where mycobacteria can reside for decades. Although macrophages are the cells mostly involved in the control of mycobacteria, DCs are also an additional reservoir for BCG (8) or M. tuberculosis (10) and, when infected, display an impaired ability to present Ag to T cells (8,9). Infected DCs and macrophages need to cooperate with other cells not only to control the infection, but also to regulate the host immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, mycobacterial infection induces a delicate equilibrium between proinflammatory and anti-inflammatory immune responses, and this is well illustrated in pulmonary granulomas where mycobacteria can reside for decades. Although macrophages are the cells mostly involved in the control of mycobacteria, DCs are also an additional reservoir for BCG (8) or M. tuberculosis (10) and, when infected, display an impaired ability to present Ag to T cells (8,9). Infected DCs and macrophages need to cooperate with other cells not only to control the infection, but also to regulate the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that BCG is an acceptable model for interactions taking place between DCs, neutrophils, and CD4 T cells in the lung with fully virulent M. tuberculosis for the following reasons: 1) the important role of IL-17 in granuloma formation has been first shown in BCG infected mice (19) and later confirmed with M. tuberculosis (18); 2) production of IL-10 by infected neutrophils in vitro and in vivo has been demonstrated both after BCG and M. tuberculosis infection (38); 3) in vivo DC infection has been shown both with BCG (8,9,54) and M. tuberculosis (55,56); and 4) recruitment of neutrophils to the site of infection has been shown both with BCG (13,57) and M. tuberculosis (58,59). We propose a model (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CD4 T cells, the phenomenon is not nearly as well characterized and understood, but there are clear indications that immune regulation and functional exhaustion take place in a number of chronic infections (18)(19)(20)(21)(22). In animal models, ongoing TB infection has recently been reported to drive T cells into a stage of terminal differentiation (23).…”
mentioning
confidence: 99%
“…In mice models, we have previously reported that adoptive transfer of M. tuberculosis-specific memory cells (from cleared infection or after subunit vaccination) can confer significant protection to challenge (30,31), and that central memory T cells (T CM ) are the most important subset responsible for this effect (30). Immune regulation exerted by inhibitory receptor signaling such as KLRG1, through the PD-1-PD-L1/2 axis, regulatory T cells, and immunosuppressive cytokines, are all mechanisms developed to avoid excess immunopathology (32); but in TB, there is increasing evidence that these pathways also play an important role in the longterm maintenance of the equilibrium needed to support chronic infection (20,21). Thus, to be successful, any novel vaccine strategy to boost BCG needs to be able to overcome or counteract all these complex signals in an environment of chronic TB infection and maintain a reservoir of specific self-renewing T cells that can mediate long-term containment.…”
mentioning
confidence: 99%